Capturing differences in dental training using a virtual reality simulator. (19th November 2016) - Mirghani, I.; Mushtaq, F.; Allsop, M. J.; Al‐Saud, L. M.; Tickhill, N.; Potter, C.; Keeling, A.; Mon‐Williams, M. A.; Manogue, M.
Abstract: Virtual reality simulators are becoming increasingly popular in dental schools across the world. But to what extent do these systems reflect actual dental ability? Addressing this question of construct validity is a fundamental step that is necessary before these systems can be fully integrated into a dental school's curriculum. In this study, we examined the sensitivity of the Simodont (a haptic virtual reality dental simulator) to differences in dental training experience. Two hundred and eighty‐nine participants, with 1 ( n = 92), 3 ( n = 79), 4 ( n = 57) and 5 ( n = 61) years of dental training, performed a series of tasks upon their first exposure to the simulator. We found statistically significant differences between novice (Year 1) and experienced dental trainees (operationalised as 3 or more years of training), but no differences between performance of experienced trainees with varying levels of experience. This work represents a crucial first step in understanding the value of haptic virtual reality simulators in dental education.